2022
DOI: 10.3847/2041-8213/ac9839
|View full text |Cite
|
Sign up to set email alerts
|

Most Planets Might Have More than 5 Myr of Time to Form

Abstract: The lifetime of protoplanetary disks is a crucial parameter for planet formation research. Observations of disk fractions in star clusters imply median disk lifetimes of 1–3 Myr. This very short disk lifetime calls for planet formation to occur extremely rapidly. We show that young, distant clusters (≤5 Myr, >200 pc) often dominate these types of studies. Such clusters frequently suffer from limiting magnitudes leading to an over-representation of high-mass stars. As high-mass stars disperse their disks ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 70 publications
0
15
1
Order By: Relevance
“…3), because gas is more bound for higher-mass stars. This positive correlation is at odds with observations that find that disc lifetimes are either independent of or anticorrelated with stellar mass (Carpenter et al 2006;Kennedy & Kenyon 2009;Bayo et al 2012;Ribas et al 2015;Pfalzner et al 2022) and should be investigated in the future.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…3), because gas is more bound for higher-mass stars. This positive correlation is at odds with observations that find that disc lifetimes are either independent of or anticorrelated with stellar mass (Carpenter et al 2006;Kennedy & Kenyon 2009;Bayo et al 2012;Ribas et al 2015;Pfalzner et al 2022) and should be investigated in the future.…”
Section: Discussioncontrasting
confidence: 68%
“…It is difficult to reconcile the results of our synthetic disc populations with observations. We find that it is particularly hard to obtain discs with characteristic lifetimes of 2 to 3 Myr according to Mamajek (2009) or Fedele et al (2010), and even less lifetimes of 5 to 10 Myr following Pfalzner et al (2022). Here, we assumed that the initial mass is constrained by the dust-mass measurements of Tychoniec et al (2018, M D /M ∼ 10 −3 ) , and dust-to-gas ratios similar to the solar initial abundance, namely f D/G = 1.49 % (Lodders 2003), combined with the predictions of internal and external photoevaporation models.…”
Section: Discussionmentioning
confidence: 75%
“…This would imply a formation timescale of ≈5-15 Myr, which would suggest formation via core accretion, which takes many Myr to operate, over rapid giant planet formation via disk instability. Typical protoplanetary disk lifetimes are 5-10 Myr for Sun-like and lower-mass (<2 M e ) stars (Pfalzner et al 2022). Other possibilities for resolving this discrepancy include a younger age of the system, young L/T transition objects being more luminous than predicted by current evolutionary models, and another planet in the system biasing the dynamical mass measurement.…”
Section: Orbit Fit and Dynamical Massmentioning
confidence: 99%
“…The lifetime of disks of the TTSs appears to be strongly correlated with the stellar mass, as disks around more massive stars tend to dissipate more rapidly than those around less massive stars (e.g., Yao et al 2018;Luhman 2022a;Pfalzner et al 2022). Most K-and M-type stars are thought to be surrounded by disks at about 1 Myr (Barenfeld et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The e-folding timescale of the disks for K-type TTSs is estimated to be 4.7 Myr (Pecaut & Mamajek 2016), while for M-type stars the disk should last much longer (Silverberg et al 2020), and the disk fraction is even still as high as about 9% at 20 Myr. Pfalzner et al (2022) suggested that low-mass stars have a median disk lifetime of 5-10 Myr. However, we should be aware that all the timescales mentioned above are for disks, not just for full disks.…”
Section: Introductionmentioning
confidence: 99%